Do Second Chances Pay Off? Evidence from a Natural Experiment with Low-Achieving Students - Aspasia Bizopoulou; Rigissa Megalokonomou; Stefania Simion (Center for Economic Studies and ifo Institute (CESifo), 2022)
In several countries, students who fail end-of-high-school high-stakes exams are faced with the choice of retaking them or forgoing postsecondary education. We explore exogenous variation generated by a 2006 policy that imposed a performance threshold for admission into postsecondary education in Greece to estimate the effect of retaking exams on a range of outcomes. Using a fuzzy regression discontinuity design and novel administrative data, we find that low-achieving students who retake national exams improve their performance by half a standard deviation, but do not receive offers from higher quality postsecondary placements. The driving mechanism for these results stems from increased competition.
Keywords: J16; I21; I23; 330; postsecondary education admission; low-achieving students; exogenous policy; fuzzy regression discontinuity design